Androgen Status in Healthy Premenopausal Women with Loss of Libido - NYUNT, A.; STEPHEN, G.; GIBBIN, J.; DURGAN, L.; FIELDING, A. M.; WHEELER, M.; PRICE, D. E. (Journal of sex & marital therapy, 2005)
Androgen deficiency may contribute to female sexual dysfunction and loss of libido. The role of the active metabolite of testosterone, dihydrotestosterone (DHT), in these conditions is uncertain. The aim of this study was to determine the role of androgens and DHT in the etiology of loss of libido in healthy women. We studied 29 premenopausal women with reduced libido (subjects) and 12 healthy females (controls). They were aged 18 to 45 years and in a stable heterosexual relationship. At 9 a.m. we took venous blood in the follicular phase for serum estradiol, total testosterone, and DHT, dehydroepiandrosterone sulfate (DHEAS), and SHBG levels. Subjects were interviewed by a psychosexual counsellor. Using the modified Wilson's sexual fantasy questionnaire ( Baumgartner, Scalora, & Huss, 2002 ) and sexual satisfaction by Golombok-Rust Inventory of Sexual Satisfaction ( GRISS Rust & Golombok, 1985, 1986 ) we assessed sexual drive. The total testosterone and DHT levels (mean ± SD) were respectively 0.97 ± 0.38 mmol/L and 0.76 ± 0.37 nmol/L in subjects and 0.97 ± 0.41 mmol/L and 0.77 ± 0.15 nmol/L in controls. The SHBG and DHEAS were respectively 65 ± 42 mmol/L and 3.76 ± 1.0 umol/L in subjects and 65 ± 29 mmol/L and 3.67 ± 2.6 in controls. The scores of the Wilson questionnaire and GRISS were respectively 21 ± 14.1 and 5 ± 2.1 in subjects and 35 ± 14.8 & 2 ± 1.2 in controls. Subjects were more likely than controls to have low income (48% versus 8%, p < 0.02), a minor illnesses (57% versus 17%, p < 0.02), a history of depression (57% versus 8%, p = 0.025) and to report sexual problems in their partners (24% versus 0%, p = 0.053). Loss of libido in otherwise healthy women may be related to relationship problem, depression, psychosocial factors, and sexual dysfunction in the partner but do not appear to be related to androgen status.